Niveles de bacitracina de zinc en dietas para cerdos landrace F1 en la fase de crecimiento. - Calero Lara, Alexandra Lucia (2013)
The investigation was run at the Experimental Farm “La María", Faculty of Animal Science, State Technical University of Quevedo (UTEQ), located at km 7 via Quevedo-El Empalme, Mocache Canton, province of Los Rios, aiming to assess reproductive parameters F1 Landrace pigs in the growth phase, fed different levels of bacitracin zinc in their diets. 0.00 mg, 200 mg, 250 mg, 300 mg, 350 mg of bacitracin zinc with the respective experimental diets with five treatments and four replication: After week of adaptation, a balanced diet of growing pigs raised levels was used, with a total of four pigs per treatment. Every 14 days the live weight of the pigs from each treatment and therefore the data was taken. The food was delivered in the first week of the experiment to 14 days, 0.750g of daily food, 14 days to 42 was provided 0.875g, and of 42 to 90 days was fed 2 kg of food. Once completed the experimental phase results showed no significant difference in feed intake, although weight gain, feed conversion and economic analysis T3 was the best treatment, with values of 56.11 kg, 2.71, and $ 0.37. Keywords: Bacitracin Zinc, F1 Landrace pigs, feed intake, weight gain, feed conversion, Economic Analysis.